Urgency Preservation of Digital Archives - Hapsari, Nurul Fikriati Ayu; Ariyani, Catharina Labore Tatiek (Record and Library Journal, 2018)
Background of the study: The presence of technology creates archives originating from conventional media transfer to digital media and archives that are presented digitally (born-digital). Digital archives that contain information on a particular subject can be the main evidence in dealing with a problem in an institution or organization as well as consideration for decision making. Purpose: The purpose of this article is to describe the importance of preservation of digital archives, especially for institutions or organizations that need information in their digital archives. Method: This research uses the literature study method by collecting literature related to the topics discussed then selecting to produce a picture of the urgency of preservation of digital archives. Findings: The results of this study note that digital archival storage media are very at risk of experiencing degradation because they are not designed to last for long periods of time. Digital archive preservation is not only considered from storage media, it is also necessary to pay attention to preservation of technology used to access digital media and intellectual preservation. Conclusion: It is hoped that preservation of digital archives for long-term preservation should already be a particular concern and a priority for the government and related institutions. So that the important information contained can still be used by future generations.